Faktor-Faktor Yang Berhubungan Dengan Ibu Hamil Dalam Melakukan Imunisasi Tetanus Toxoid - desti widya astuti (STIKES Citra Delima Bangka Belitung, 2022)
Tetanus Toxoid (TT) immunization is a purified tetanus toxin that is given to infants, children and mothers in an effort to provide protection against tetanus. The purpose of this study was to determine the factors associated with pregnant women in immunizing tetanus toxoid at the Pasar Prabumulih Public Health Center in 2021. This study uses an Analytical Survey using a Cross Sectional approach. The population of this study were pregnant women who were immunizing against tetanus toxoid. The number of samples in this study was 252 respondents. In the univariate analysis, it was found that from 252 respondents, it was found that respondents with high risk age were 141 respondents (56.0%) and respondents with low risk age were 111 respondents (44.0%). ,2%) and respondents with low parity as many as 123 respondents (48.8%) and respondents with higher education as many as 136 respondents (51.2%) and respondents with low education as many as 116 respondents (46.0%). Conclusion showed maternal age had a significant relationship with tetanus toxoid immunization (p value 0.000), maternal parity had a significant relationship with tetanus toxoid immunization (p value 0.000), and maternal education had a significant relationship with tetanus toxoid immunization (p value 0.000 ). Further research can be done with other variables with the incidence of tetanus toxoid in pregnant women.